The tadpole of Physalaemus lateristriga (Steindachner, 1864) (Anura: Leptodactylidae): external and oral internal morphology - Mello, Caio Marinho; Da Silva Gonçalves, Darlene; Rossa-Feres, Denise De Cerqueira; Conte, Carlos Eduardo (Zootaxa, 2021)
The genus Physalaemus Fitzinger is composed by 49 species (Frost 2020), which are grouped in two major clades (Lourenço et al. 2015), the Physalaemus cuvieri and P. signifer clades. Within the P. cuvieri clade, five species groups are recognized: P. biligonigerus, P. cuvieri, P. gracilis, P. henselii, and P. olfersii (Lourenço et al. 2015). According to Lourenço et al. (2015), seven species are assigned to the P. olfersii group: P. feioi, P. insperatus, P. lateristriga, P. maximus, P. olfersii, P. orophilus, and P. soaresi. Regarding their larval stage, four species have their tadpoles described for external morphology: P. maximus, P. olfersii, P. orophilus, and P. soaresi (Weber et al. 2005; Baêta et al. 2007; Giaretta et al. 2009; Pezzuti et al. 2019); two of them have their tadpoles described for oral internal morphology: P. maximus and P. soaresi (Ruggeri & Weber 2012). Herein, we describe the external and oral internal morphology of tadpole of P. lateristriga from Paraná State, southern Brazil, and compare them to the known tadpoles of the P. olfersii group.